2001
DOI: 10.1046/j.1365-2419.2001.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth of larval and early juvenile Japanese anchovy, Engraulis japonicus, in the Kuroshio‐Oyashio transition region

Abstract: Larvae, juveniles, and adults of Japanese anchovy, Engraulis japonicus, were distributed throughout the Kuroshio‐Oyashio transition region off northern Japan as far offshore as 170°E in 1996 and 1997. The growth trajectories of individual larvae and early juveniles were backcalculated using the biological intercept method based on the allometric relationship between otolith radius and somatic length. Mean larval growth rates ranged from 0.49 to 0.71 mm day–1 in the transition region, and were comparable to tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
74
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 16 publications
8
74
0
Order By: Relevance
“…3). In the Atlantic cod (Gadus morhua) and Japanese anchovy (Engraulis japonicus), it has been suggested that individuals with high growth rates in their early life stages have a higher probability of survival and that this early growth determines the success or failure of recruitment (Meekan and Fortier, 1996;Takahashi et al, 2001;Takahashi and Watanabe, 2004;Takasuka et al, 2004). On the other hand, the results of the present study show that individuals of jack mackerel with slower growth rates could survive and be recruited successfully to the stock.…”
Section: Growth and Survivalmentioning
confidence: 41%
“…3). In the Atlantic cod (Gadus morhua) and Japanese anchovy (Engraulis japonicus), it has been suggested that individuals with high growth rates in their early life stages have a higher probability of survival and that this early growth determines the success or failure of recruitment (Meekan and Fortier, 1996;Takahashi et al, 2001;Takahashi and Watanabe, 2004;Takasuka et al, 2004). On the other hand, the results of the present study show that individuals of jack mackerel with slower growth rates could survive and be recruited successfully to the stock.…”
Section: Growth and Survivalmentioning
confidence: 41%
“…The average biomass of copepods is greater in the northern part of the transition region dominated by cold-water species than in the southern part dominated by warm-water species (Odate 1994). Growth and developmental rates of larval Engraulis japonicus were faster in the SW waters than in the northern or eastern waters in the transition region (Takahashi 2001). In the spatially and temporally variable environments in the transition region, the probability of an E. japonicus larva surviving to recruitment will be variable, depending on the environmental conditions in which it occurs.…”
Section: Abstract: Growth Rate · Survival · Otolith Increment Width mentioning
confidence: 95%
“…The main nursery and feeding grounds were concluded to shift from the coastal waters to the eastern offshore waters off northern Japan with the increase in population size. Larval, juvenile and adult E. japonicus were distributed in the eastern offshore waters off northern Japan, the Kuroshio-Oyashio transition region, in the 1950s and 1990s when the population sizes were large (Odate 1957, Takahashi et al 2001. The distribution range of the Japanese sardine Sardinops melanostictus have also been shown to expand during periods of large population size to the eastern offshore waters in the transition region and subarctic waters (Kuroda 1991).…”
Section: Abstract: Growth Rate · Survival · Otolith Increment Width mentioning
confidence: 99%
“…The larval distribution of this species extended from coastal to offshore waters in the transition region, and the larvae formed one of the main components of the ichthyoplankton (Kubota et al 2001, Takahashi et al 2001. Recently, Sassa & Kawaguchi (2004) suggested that the absence of competition for prey between E. japonicus and coexisting Diaphus garmani larvae in the transition region was the result of their diet segregation.…”
Section: Possible Prey Competition Among Fish Larvae In the Transitiomentioning
confidence: 99%
“…Interspecific differences among the feeding habits of these larvae, which are spawned in the transition region, together with 3 other common myctophid larvae that are spawned in the Kuroshio region and transported into the study area (Sassa 2001, Sassa & Kawaguchi 2004, are discussed in relation to mouth size. Possible competition for prey among the larvae of the 3 myctophids and Japanese anchovy Engraulis japonicus is also discussed, since E. japonicus larvae are the most dominant among commercially important fish larvae in this study area and their habitats often overlap spatiotemporally (Kubota et al 2001, Sassa 2001, Takahashi et al 2001.…”
Section: Introductionmentioning
confidence: 99%